Analysis of atmospheric turbulence in the upper layers of sea fog - 李永平 郑运霞 (Chinese journal of oceanology and limnology, 2015)
Atmospheric turbulence plays a vital role in the formation and dissipation of fog. However, studies of such turbulence are typically limited to observations with ultrasonic anemometers less than 100 m above ground. Thus, the turbulence characteristics of upper fog layers are poorly known. In this paper, we present 4-layers of data, measured by ultrasonic anemometers on a wind tower about 400 m above the sea surface; we use these data to characterize atmospheric turbulence atop a heavy sea fog. Large differences in turbulence during the sea fog episode were recorded. Results showed that the kinetic energy, momentum flux, and sensible heat flux of turbulence increased rapidly during the onset of fog. After onset, high turbulence was observed within the uppermost fog layer. As long as this turbulence did not exceed a critical threshold, it was crucial to enhancing the cooling rate, and maintaining the fog. Vertical momentum flux and sensible heat flux generated by this turbulence weakened wind speed and decreased air temperature during the fog. Towards the end of the fog episode, the vertical distribution of sensible heat flux reversed, contributing to a downward momentum flux in all upper layers. Spatial and temporal scales of the turbulence eddy were greater before and after the fog, than during the fog episode. Turbulence energy was greatest in upper levels, around 430 m and 450 m above mean sea level (AMSL), than in lower levels of the fog (390 m and 410 m AMSL); turbulence energy peaked along the mean wind direction. Our results show that the status of turbulence was complicated within the fog; turbulence caused fluxes of momentum and sensible heat atop the fog layer, affecting the underlying fog by decreasing or increasing average wind speed, as well as promoting or demoting air temperature stratification.